2022
DOI: 10.1007/s00068-022-02108-5
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and management of paediatric pelvic fractures: a changing landscape based on skeletal maturity

Abstract: Introduction Paediatric pelvic fractures (PPFs) are uncommon but signify serious trauma. A comprehensive multidisciplinary approach is needed due to a high number of associated injuries. This study aims to retrospectively analyse PPFs over a 5-year period and evaluate how advancing skeletal maturity changes fracture patterns and management plans. Methods The trauma database was retrospectively reviewed for pelvic fractures in patients aged ≤ 18 years. Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It could also be that acetabular fractures in children tend to occur after triradiate cartilage closure. Lu et al 19 reported that children with skeletal immaturity were less likely to have acetabular fractures compared with skeletally mature patients (12% versus 37.5%), and no acetabular fractures were found in our skeletally mature patients, which may be related to both the age of the child and the type of injury. For stable and unstable fractures, we found higher ISSs for stable fractures, meaning that stable fractures may be more likely to be combined with other injuries; for unstable fractures, owing to partial energy absorption, the associated injuries are less severe.…”
Section: Discussionmentioning
confidence: 44%
“…It could also be that acetabular fractures in children tend to occur after triradiate cartilage closure. Lu et al 19 reported that children with skeletal immaturity were less likely to have acetabular fractures compared with skeletally mature patients (12% versus 37.5%), and no acetabular fractures were found in our skeletally mature patients, which may be related to both the age of the child and the type of injury. For stable and unstable fractures, we found higher ISSs for stable fractures, meaning that stable fractures may be more likely to be combined with other injuries; for unstable fractures, owing to partial energy absorption, the associated injuries are less severe.…”
Section: Discussionmentioning
confidence: 44%
“…10,15 Furthermore, displaced sacroiliac joint (SIJ) disruptions are associated with markedly higher risk of more serious chest, intra-abdominal, and pelvic organ and vascular injuries with considerable morbidity and mortality. 10,16-18…”
Section: Relevant Anatomic Peculiarities Of the Immature Pediatric Pe...mentioning
confidence: 99%
“…10,15 Furthermore, displaced sacroiliac joint (SIJ) disruptions are associated with markedly higher risk of more serious chest, intraabdominal, and pelvic organ and vascular injuries with considerable morbidity and mortality. 10,[16][17][18] In a study of 9,684 patients younger than 17 years with pelvic fractures from the German pelvic trauma register, children with severe pelvic injuries (abbreviated injury scale (AIS) pelvis $ 2) had higher incidence of severe chest and abdominal injuries (AIS $ 2) with an overall mortality rate of 10.1% compared with 7.9% with AIS pelvis , 2. 10 In a pelvic trauma study from the US national trauma data bank of 5,325 children (younger than 13 years), 4,052 adolescents (13 to 17 years), and 28,407 adults (18 to 54 years), children had the highest odds of death after sustaining pelvic injuries compared with that in adolescents and adults with an overall mortality rate of 10% compared with 6.8% in adolescents and 8.5% in adults.…”
mentioning
confidence: 99%